The Use of Code Swtiching by Chef Juna and Deddy Corbuzier in Deddy Corbuzier Podcast - Nisicha, Theresya Grace; Marpaung, Marlin Steffi (STKIP Yapis Dompu, 2023)
Code-switching has become a characteristic or pattern of communicative change in contemporary generation. This effect occurs in Indonesian culture, which was acculturated with a foreign language, and code-switching can let them construct a simple phrase to declare that is not available in their own language. It is frequently heard on various national entertainment shows, by content producers on YouTube, and in podcasts. The main objective of this research paper is to explicate which type and kind of code switching is more widespread when the two speakers speak in Deddy Corbuzier's podcast. This study collects data using qualitative methodologies for sociolinguistic phenomena and documentation procedures. In this study, Poplack theory is applied to examine the different forms of code switching. The authors encountered three patterns of code-switching: Tag-switching, inter-sentential code-switching, and intra-sentential code-switching are part of code-switching. Based upon the outcomes of the data acquired from the Deddy Corbuzier Podcast, the researchers summarize that the form of switching code that is most commonly employed in communication is Inter Sentential Code Switching.